Digital Transformation and the Strategic Role of Human Resources in Improving Organizational Performance - Djunaedi, Djunaedi (MSJ : Majority Science Journal, 2025)
Digital transformation has become a major factor in improving organizational performance in the modern era. One important aspect in the success of digital transformation is the strategic role of human resources (HR). This study aims to analyze how digital transformation affects the role of HR and its impact on organizational performance. The method used in this study is the Systematic Literature Review (SLR), which allows for in-depth analysis of various previously published studies. The stages in the SLR include identifying research questions, searching for literature on trusted academic sources such as Scopus, IEEE Xplore, ScienceDirect, Google Scholar, and SpringerLink, and synthesizing findings related to the implementation of digitalization and HR management. The keywords used in the search include "Digital Transformation and Human Resource Strategy," "Impact of Digitalization on Organizational Performance," and "Challenges in Digital Transformation." The results of the study show that digital transformation has a significant impact on the strategic role of HR in organizations. Technology not only automates administrative processes but also enables HR to improve the effectiveness of talent management, accelerate organizational adaptation to change, and strengthen a culture of innovation. However, the success of digitalization depends not only on technology, but also on HR readiness and management support. Therefore, organizations need to implement appropriate policies, training strategies, and change management to ensure that digital transformation runs optimally and improves overall organizational performance